GmFT2a polymorphism and maturity diversity in soybeans. - Bingjun Jiang; Yanlei Yue; Youfei Gao; Liming Ma; Shi Sun; Cunxiang Wu; Wensheng Hou; Hon-Ming Lam; Tianfu Han (PLoS ONE, 2013)
BACKGROUND:Soybean is a short-day crop of agricultural, ecological, and economic importance. The sensitive photoperiod responses significantly limit its breeding and adaptation. GmFT2a, a putative florigen gene with different transcription profiles in two cultivars (late-maturing Zigongdongdou and early-maturing Heihe 27) with different maturity profiles, is key to flowering and maturation. However, up to now, its role in the diverse patterns of maturation in soybeans has been poorly understood. METHODS:Eighty varieties, including 19 wild accessions, covering 11 of all 13 maturity groups, were collected. They were planted in pots and maintained under different photoperiodicity conditions (SD, short day; LD, long day; and ND, natural day). The day to first flowering was recorded and the sensitivity to photoperiod was investigated. Polymorphisms in the GmFT2a coding sequence were explored by searching the known SNP database (NCBI dbSNP). The GmFT2a promoter regions were then cloned from these varieties and sequenced. Further polymorphism and association analyses were conducted. RESULTS:These varieties varied greatly in time to first flowering under ND and exhibited a consecutive distribution of photoperiod sensitivity, which suggested that there is rich diversity in flowering time. Furthermore, although GmFT2a had only one known synonymous SNP in the coding sequence, there were 17 haplotypes of the GmFT2a promoter region, HT06 of which was extremely abundant. Further association analysis found some SNPs that might be associated with day to first flowering and photoperiod sensitivity. CONCLUSION:Although GmFT2a is a key flowering gene, GmFT2a polymorphism does not appear to be responsible for maturity diversity in soybean.